APPLICATION OF FLUE GAS WET DESULFURIZATION METHOD AT ROVINARI COAL-FIRED POWER PLANT –PROCESS PERFORMANCE - Lucica Anghelescu (Analele Universităţii "Constantin Brâncuşi" din Târgu Jiu: Seria Inginerie, 2018)
The power plants pollutethe atmosphere, through the chimneys, continuously and constantly, huge volumes of flue gascontaining relatively small concentrations of pollutants and particles. As a result, conventional boiler houses with conventional boilers are considered to be stationary sources ofmajor anthropogenic emissions.Pollutants present in flue gaswhen discharged into the mouth of the chimney, called primary pollutants (SO2, SO3, NO2, CO2, CO, etc.), can remain as such and aretherefore unchanged in smoke (CO2) or, on the contrary, they can be converted into secondary pollutants (NO, NO2, etc.).Both primary and secondary pollutants may enter into reaction chains with other pollutants or gases that enter into the natural air composition and may favor the formation of tertiary pollutants (ex.ozone).